Neglected Penile Rubber Ring and Its Consequences: A Case Report (Janaki Medical College Journal of Medical Science, 2025)
Background and objectives: Penile rings are constriction devices used to enhance erection by limiting venous outflow. Here, we present a case of neglected Penile Rubber Ring in man with penile swelling following foreskin retraction.Presentation of Case: A case of a 62-year-old man who presented in our surgical OPD with sudden penile swelling and pain. Surgical intervention was done with the operative finding of a penile rubber ring inserted 14 years back, which had remained asymptomatic. It was kept for sexual enhancement. The ring was removed, and the patient had an uneventful postoperative period with full recovery.Discussion: The chronic presence of the penile rubber ring led to sebum accumulation and local inflammation, predisposing him to sudden penile swelling and pain. Early surgical intervention was critical in preventing further complications.Conclusion: This case suggests the importance of considering retained foreign bodies in patients presenting with penile swelling and the need for early surgical intervention to prevent it’s consequences.